Dose–response effects of TPI ASM8 in asthmatics after allergen - Gauvreau, G. M.; Pageau, R.; Séguin, R.; Carballo, D.; Gauthier, J.; D’Anjou, H.; Campbell, H.; Watson, R.; Mistry, M.; Parry‐Billings, M.; Killian, K.; Renzi, P. M. (Allergy (Copenhagen), 2011)
To cite this article: Gauvreau GM, Pageau R, Séguin R, Carballo D, Gauthier J, D’Anjou H, Campbell H, Watson R, Mistry M, Parry‐Billings M, Killian K, Renzi PM. Dose–response effects of TPI ASM8 in asthmatics after allergen. Allergy 2011; 66: 1242–1248. Background:  TPI ASM8 contains two modified antisense oligonucleotides (AON) targeting the beta subunit (βc) of the IL‐3, IL‐5, GM‐CSF receptors and the chemokine receptor CCR3. A previous study suggested that TPI ASM8 had broader effects than just inhibition of eosinophils in asthmatics. Objective:  We assessed whether TPI ASM8 caused a dose‐dependent attenuation in the inflammatory and physiological changes after inhaled allergen challenge (AIC). Methods:  This single‐center, open‐label, stepwise‐ascending dose study was conducted in fourteen stable, mild allergic asthmatics. Following placebo AIC, subjects underwent AIC after 4 days treatment with 1, 2, and 4 mg BID and finally 8 mg once daily (OD) of TPI ASM8, inhaled via the I‐Neb™ nebuliser. Treatments were separated by 2–3‐week washout periods. Results:  TPI ASM8 was safe and well tolerated at all doses. TPI ASM8 8 mg OD reduced eosinophils in sputum after AIC (by 60.9% at 7 h and 68.4% at 24 h post‐AIC, P = 0.016 and P = 0.007, respectively). Additionally, TPI ASM8 8 mg OD significantly attenuated the early and late airway responses as shown by the reduction in the area under the curve by 45% (P = 0.016) and 59%, (P = 0.0015), respectively, the increase in eosinophil cationic protein (ECP) by up to 57% (P = 0.021), and airway responsiveness to methacholine by more than 1 doubling dose (P = 0.012). A dose–response relationship was noted, and efficacy was maintained with once per day administration. Conclusions:  TPI ASM8 attenuated a broad range of inflammatory and physiological changes after AIC, suggesting that CCR3, IL‐3, and GM‐CSF also are important targets for the management of asthma.